{Sedimentological processes in the southern margin of the Cretan Sea (NE Mediterranean)} - Chronis, G.; Lykousis, V.; Anagnostou, C.; Karageorgis, A; Stavrakakis, S; Poulos, S. (Progress in Oceanography, 2000)
The Cretan Basin can be characterized as a back-arc basin of the Hellenic Trench System, that is related to the subduction zone of the African Plate under the Eurasia Plate. The study area includes the narrow and relatively steep (gradient 1.5°) continental shelf of the island of Crete followed by the steep slope (2°–4°) and the rather flat deeper part of the Cretan basin (water depths >1700 m). Surficial sediments of the coastal zone are coarser and of terrigenous origin, while in deeper waters finer sediments, of biogenic origin, are more abundant. Sand-sized calcareous sediment accumulations, identified in middle-lower slope, may be attributed to the aggregation of seabed biogenic material related to the near bed current activity. High resolution profiles (3.5 kHz) taken from the inner shelf shows a typical sigmoid-oblique progradational configuration, implying prodelta sediment accumulation during the Holocene. In the upper-middle slope, sub-bottom reflectors indicate continuous sedimentation of alternating fine and/or coarse grained material. Small-scale gravity induced synsedimentary faults appeared, locally. In contrast, a series of gravity induced faults, identified in the lower slope, are associated with sediment instabilities due to seismotectonic activity. Sediment cores taken from the shelf-break consists of calcareous muddy sand with small amounts of terrigenous silt and fine sand, while the cores recovered from the middle slope has revealed a more homogeneous fine sediment texture of hemipelagic deposition. The prevailing accumulation processes in the southern margin of the Cretan basin are: (i) prodelta deposition in the inner-middle shelf; (ii) settling from bottom nepheloid layers in the shelf and upper slope; (iii) calcareous sediment formation due to settling from suspension and post accumulation aggregation (middle-lower slope); (iv) long-term episodic sediment gravity processes in the lower slope; and (v) to a lesser extent, redeposition from resuspension due to gravity processes and bottom currents.